Relectura de la obra lucana a partir de la pedagogía de la liberación - Mongui Casas, Leonardo (2015)
This thesis seeks to analyze the Lukan corpus from the pedagogic criteria presented by a Pedagogy of Liberation, thus re-reading Luke’s Gospel and the Act of the Apostles with a view liberate and transform the social environment. In doing so, five elements of the Pedagogy of Liberation are taken into account: a) the role of the oppressed at the heart of liberating action; b) conversion-transformation or as a goal; c) the role of women in transformative action; d) new ways and relationships regarding teaching; e) the community as a privileged setting for learning. These elements will be analyzed from the pedagogic criteria presented by Freire and from a biblical theology present in the teachings of the Master. This work concludes by highlighting the importance of justice in the Lukan corpus, resulting in personal and communal conversion-transformation, as a way to change structural oppression. It recovers the importance given by the Lord to women among his disciples, giving them an important role in the building of the Kingdom of God, thus restoring human beings to their proper dignity as children of God in Jesus Christ.